Antimicrobial Peptides: Avant-Garde Antifungal Agents to Fight against Medically Important Candida Species - Gina P. Rodríguez-Castaño; Frank Rosenau; Ludger Ständker; Carolina Firacative (MDPI AG, 2023)
Expanding the antifungal drug arsenal for treating Candida infections is crucial in this era of the rising life expectancy of patients with immunosuppression and comorbidities. Infections caused by Candida species are on the rise, including those caused by multidrug-resistant strains or species, and the list of antifungals approved for the treatment of these infections is still limited. Antimicrobial peptides (AMPs) are short cationic polypeptides whose antimicrobial activity is under intense investigation. In this review, we present a comprehensive summary of the AMPs with anti-Candida activity that have undergone successful preclinical or clinical trials. Their source, mode of action, and animal model of infection (or clinical trial) are presented. In addition, as some of these AMPs have been tested in combination therapy, the advantages of this approach, as well as the studied cases that have used AMPs and other drugs concomitantly to fight Candida infections, are described.